Evaluation of Phenotypic Methods to Identify Extended Spectrum Beta-lactamase (ESBL) Producing Gram negative Bacteria (Bangladesh Journal of Medical Microbiology, 2017)
Extended spectrum beta-lactamase (ESBL) producing Gram negative bacteria are usually multiple drug resistant and their cephalosporin and aztreonam resistance is not reliably detected by susceptibility tests.This study was carried out to find out a cost effective easy standard method to identify ESBL producing bacteria in a laboratory associated with tertiary care hospital and to determine the incidence of ESBL positive bacteria isolated from different clinical specimens. Thereby isolated 124 Gram negative bacteria from various samples were subjected to screening test, double disc synergy test (DDST)and E test ESBL method.Screening test detected 69.35%, DDST identified 37.1% and E test ESBL method confirmed 55.65% ESBL producing strains. Screening test and DDST was compared to E test ESBL method. Considering E test as standard the sensitivity and specificity of screening test were 97.10% and 65.45% respectively and that of DDST were 62.31% and 94.55% respectively. Low specificity of screening test reflects detection of many false positive strains and low sensitivity of DDST signals many missed identification. This study suggested the use of E test ESBL method to confirm screening positive ESBL isolates at microbiology laboratory.Bangladesh J Med Microbiol 2014; 08 (01): 21-24